Preventing sexual harm : positive criminology and sexual abuse - Kewley, Stephanie; Pemberton, Sarah; Rahman, Mohammed (London : Routledge, 2021)
Preventing Sexual Harm provides an overview of current criminal justice strategies for tackling sexual violence, and highlights existing positive criminological approaches that could help prevent sexual abuse and harm. Sexual violence is a complex, multi-faceted crime. Its causes and consequences are both multiple and enduring and our understanding of sexual violence is embedded within our social, cultural, and political constructs. As such, a response to sexual violence ought to be equally complex and multi-faceted. Alternative approaches might therefore be needed, such as positive criminology. This book explores positive criminology as a mechanism to reduce the risk of recidivism, eradicate harm, prevent reoffending as well as to help reintegrate those with histories of sexual abuse back into the community. In light of recent historic cases of sexual abuse and poor institutional response to these allegations, it opens with an overview of the current landscape of sexual offending. The book then reviews the current positive criminological approaches already in existence in the effort to prevent sexual abuse by outlining the approach of positive criminology and by demonstrating the many gaps in practice that might benefit from this new way of working to prevent sexual abuse. By highlighting that an alternative response to sexual violence is needed, and by presenting the idea that a positive criminological paradigm is worthy of further examination, this book will be of great interest to scholars of criminology, criminal justice, and forensic psychology.
Introduction -- 1. Definition, causes, and prevalence of sexual abuse -- 2. Current approaches to sentencing and management -- 3. Current approaches to the assessment of sexual offending -- 4. Current approaches to the treatment of sexual offending -- 5. Prevention strategies of sexual harm -- 6. Positive criminology as an alternative -- 7. Current positive criminology applications in terms of assessment -- 8. Current positive criminology applications in terms of treatment and management -- 9. Religion, spirituality, and positive criminology -- Conclusion -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Sex crimes -- Prevention; Sex offenders -- Rehabilitation; Criminal justice, Administration of; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Forensic Psychology; PSYCHOLOGY / Social Psychology